2021
DOI: 10.1021/acsagscitech.1c00070
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Resolution Monitoring to Determine the Preferential Transport of Enteric Bacteria and Antibiotic Resistance Genes from Liquid Pig Manure Applied to Tile-Drained Arable Fields

Abstract: The degree of preferential transport through soil is crucial to its ability to serve as a barrier to prevent fecal pollutants from reaching surface water and groundwater when liquid manure is applied to arable tile-drained fields. Over a seven-month period, drainage was analyzed for enteric bacteria (CFU), genes [16S, tet(W), and Intl1], turbidity, and two anions (nitrate and chloride) following application of liquid pig manure to two tile-drained arable clayey till fields. Combined with high-resolution monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Stumpp and Maloszewski (2010) revealed in a lysimeter study that evapotranspiration from barley was ∼50% greater and preferential flow 75% less than from maize, which could indicate that crop type influences the risk of ARGs and MGEs leaching to aquatic environments. A study from the Silstrup field in 2015, where maize was planted, revealed more frequent drainage during the summer months (Bech et al., 2021). Reduced preferential flow may be explained by increased plant cover that would prevent precipitation reaching the bare soil surface, where the fraction that reached the soil surface, would infiltrate into a dense root zone where plant uptake would reduce infiltration into the subsurface.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stumpp and Maloszewski (2010) revealed in a lysimeter study that evapotranspiration from barley was ∼50% greater and preferential flow 75% less than from maize, which could indicate that crop type influences the risk of ARGs and MGEs leaching to aquatic environments. A study from the Silstrup field in 2015, where maize was planted, revealed more frequent drainage during the summer months (Bech et al., 2021). Reduced preferential flow may be explained by increased plant cover that would prevent precipitation reaching the bare soil surface, where the fraction that reached the soil surface, would infiltrate into a dense root zone where plant uptake would reduce infiltration into the subsurface.…”
Section: Discussionmentioning
confidence: 99%
“…The 16S gene was amplified with primer pair 1369F and 1492R (Suzuki et al, 2000), and the intI1 gene was amplified by primer pair LC1 and LC5 (Barraud et al, 2010), with an actual detection limit from 21 intI1 ml −1 drainage. For details on qPCR protocols, see Bech et al (2021). Briefly, PCR amplification was performed in 30-μl reactions containing 15 μl Lo-Rox Probe Mix (PCR Biosystems), 1.2 μl of both primers (100 pmol μl −1 ), 0.6 μl probe (Eurofins Genomics), 11 μl water, and 1 μl DNA template.…”
Section: Qpcrmentioning
confidence: 99%
See 3 more Smart Citations